Partisipasi Masyarakat Nagari dalam Meningkatkan Pembangunan Sarana dan Prasarana Nagari di Nagari Ladang Panjang Kabupaten Pasaman - Rici Desriana Putri; Hasbullah Malau (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2021)
This study aims to determine community participation in the development of village facilities and infrastructure in Nagari Ladang Panjang, Pasaman Regency. This community partipation is seen from how the community responds to conditions in the long field area, such as community participation in the development of village facilities and infrastructure. The research method used in this study is a qualitative descriptive research method that describes phenomena that actually occur in the field. The data source obtained through the interview process with informants and documents related to research. Data collection techniques are by means of observation, documentation and interviews. The data analysis technique used is an interactive analysis technique which consists of three components, namely data reduction, data presentation, and conclusion drawing. The results showed that community participation in the development of village facilities and infrastructure in Nagari Ladang Panjang was still lacking. In the construction of the new village guardian's office, for example, the community was reluctant to give away their land for free, even though in the end the village was able to convince the community to donate their land to build a new Nagari guardian office. In addition, not many people are willing to attend the deliberations for village development organized by the nagari government, this indicates a lack of public awareness or participation in village development in Nagari Ladang Panjang. Therefore, there is a need for approaches and counseling by the village government to the community on the importance of community participation in village development.